SISTEM MANAJEMEN OPERASIONAL PENDAFTARAN PENDUDUK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DEPOK - Retnasari, Tri (www.bsi.ac.id, 2015)
As arranged in section 14 sentence 1 Statute I. fonts Number 32 Years 2004 that mandatory business that becomes kewenangan Local Government for Regency / City, cover for example “ demography Service and Civil Registry ” so needful effort renders demography administration order at Depok's City, and needs to be behaved by serious ala in particular by bound up party with ministering process at demography area. With be established UU Number 23 Years 2006 About demography Administration and Number Government regulations 37 Years 2007 about performing regulations, substantially have no more discrimination in demography administration. In is in fact is still a lot of society that haven't known and understands intended legislation regulation. So needs to be performed its socialization hits the importance for demography document continually. Base object that is analysed which is on part on duty Depok's demography and Civil Registry, officer that handle resident registration which is islandic mutation section just 1 person whereas for requisition what do want to do resident move bases reporting on totaled previous moon of all district which is 2.415 profferings. so In colonist registration handle this there are some about problem which shall be noticed. With be designed system a new one utilize information technology is expected gets to help waters down data processing at sectioned demography and waters down task Officer that handle resident registration and penyediaan is reporting to Demography Area head . Keywords: Management system, Demography administration, Information technology.